Handling position and application of Azospirillum brasilense influence agronomic cassava characters (Research, Society and Development, 2022)
The management of the cassava crop is what determines the productive potential, being in many cases neglected, as it is considered a rustic crop that responds poorly to agricultural inputs. The objective of this work was to evaluate the development of cassava as a function of the position of the manioc in combination with Azospirillum brasilense. The experimental design used was completely randomized, with a 2x2 factorial design, one factor being the positioning [horizontal (PH) and vertical (PV)] and the other the application of A. brasilense [with (+Azos) and without (-Azos)], with 20 replicates per treatment. At 165 days after planting (DAP) the variables: stem diameter (SD), number of shoots (NS), main shoot height (MSH) and leaflet length (LL) were evaluated at an interval of 30 days. At 285 DAP in the final collection, the weight of the part area (WPA), the number of commercial roots (NCR) and the total production (TP) were evaluated. Multivariate principal component (PC) analyzes were performed. The first two PC retain >88% of the data variability on most of the measured variables. Morphological development is stimulated from 165 DAP to 285 DAP, thus generating the highest productivity of cassava in the association of PH+Azos. The horizontal planting position is the best option in the cassava crop, and together with the fixation and better availability of N by A. brasilense, they promote the best performance of the crop.